Philippine medical thesaurus on anatomy endocrine system, fluids and secretions, nervous system, respiratory system and sense organs in Cebuano - Pueblos, Kurt Roy S.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Medical informatics is the integrative discipline that arises from the synergistic application of computational, informational, cognitive, organizational, and other sciences whose primary focus is the acquisition, storage, and use of information in the health/biomedical domain (Hersh, 2003). It was borne from the need to develop techniques and tools concerning the organizational management of information in support of medical research, education, and patient care.
This study is part of a project entitled Philippine Medical Thesaurus that would provide standardized medical terms arranged according to their semantic relationships and translated into major Philippine languages. This research focused on translating medical terms from the subcategories Endocrine system, Fluids and Secretions, Nervous System, Respiratory System and Sense Organs of the Medical Subject Headings into Cebuano.
This study produced 186 Cebuano main entry terms and 24 terms with definitions only out of the 536 MeSH terms used. These results will provide a framework for establishing a unified Philippine Medical Thesaurus.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Cebuano -- Medicine; Subject headings, Cebuano -- Endocrine system; Subject headings, Cebuano -- Respiratory system; Cebuano language -- Medical Cebuano